Development of Government Accounting Modules to Improve Student Competence: A Conceptual Study - Saleh, Fadli Moh.; Furqan, Andi Chairil; Masdar, Rahma; Usman, Rudy; Betty, Betty (Universitas KH. Abdul Chalim Mojokerto, 2026)
The development of government accounting learning modules is an urgent need to improve the quality of higher education, especially in accounting study programs in Indonesia. Structured, systematic, and real-practice-based learning modules are expected to be able to bridge the gap between the theory and implementation of government accounting. This article aims to conceptually analyze the urgency of developing government accounting learning modules, with an emphasis on needs evaluation, conceptual design, and technology-based implementation strategies. The research method used is quantitative - qualitative through literature review and evaluative analysis of previous research. The results of the analysis show that there are three main aspects that must be considered: (1) the integration of theory and practice through case studies and simulations, (2) the use of active learning methods to increase student involvement, and (3) the use of digital technology to expand access and flexibility of learning. This article provides a theoretical contribution in the form of a conceptual framework for the development of government accounting modules, while offering practical implications for lecturers and higher education institutions in improving learning effectiveness. The implications of this research are not only relevant for improving the quality of accounting graduates, but also support the achievement of transparent and accountable public financial governance in Indonesia.